Initiation and/or re-initiation of drug use among people who use drugs in Vancouver, Canada from 2021 to 2022: a prospective cohort study - Anjali Sergeant; Paxton Bach; Jingxin Lei; Kora DeBeck; M-J Milloy; Kanna Hayashi (BMC, 2024)
Abstract Objectives Widespread health service disruptions resulting from the COVID-19 pandemic coincided with a dramatic increase in overdose deaths among people who use drugs (PWUD) in Vancouver, Canada. Those with a history of injection drug use are known to be at heightened risk of substance-associated harms. Drug use patterns and associated sociodemographic and health care utilization trends have been understudied in this population since the pandemic onset. We sought to understand patterns of drug use initiation and/or re-initiation among people with a history of injection drug use (IVDU). Methods Data were obtained from three harmonized prospective cohort studies of PWUD in Vancouver. Participants with a lifetime history of IVDU who responded to a survey between June 2021 and May 2022 were included. The primary outcome variable was a composite of substance use initiation and re-initiation over the study period, labelled as drug (re)-initiation. A multivariable generalized linear mixed-effects model was used to examine factors associated with self-reported (re)-initiation of substance use over the past six months. Results Among 1061 participants, the median age was 47 years at baseline and 589 (55.5%) identified as men. In total, 183 (17.2%) participants reported initiating and/or re-initiating a drug, with 44 (4.1%) reporting new drug initiation and 148 (14.0%) reporting drug re-initiation (9 participants responded 'yes' to both). Overall, unregulated stimulants (e.g., crystal methamphetamine and cocaine) were the most common drug class (re-)initiated (n = 101; 55.2%), followed by opioids (n = 74; 40.4%) and psychedelics (n = 36; 19.7%). In the multivariable analysis, (re-)initiation of drug use was independently associated with recent IVDU (adjusted odds ratio [AOR] 2.62, 95% confidence interval [CI] 1.02, 6.76), incarceration (AOR 3.36, CI 1.12, 10.14) and inability to access addiction treatment (AOR 4.91, 95% CI 1.22, 19.75). Conclusions In an era impacted by the intersecting effects of the COVID-19 pandemic and the overdose crisis, nearly one in five PWUD with a history of IVDU began using a new drug and/or re-started use of a previous drug. Those who reported drug (re-)initiation exhibited riskier substance use behaviours and reported difficulty accessing treatment services. Our findings underscore the need to provide additional resources to support this high-risk population.